2014
DOI: 10.1002/acp.3001
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding Youth Interrogation Rights: The Effect of Grade Level and Reading Complexity of Youth Waiver Forms on the Comprehension of Legal Rights

Abstract: Summary: The extent to which youths understand their interrogation rights was examined. High school students (N = 160) from five different grades were presented with one of two Canadian youth waiver forms-varying widely in reading complexity-and tested on their knowledge of their legal rights. Results showed that comprehension of both waiver forms was equally deficient, and systematic misunderstandings of vital legal rights were discovered (e.g., the right to remain silent). There was also a positive linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 35 publications
(39 reference statements)
6
33
1
Order By: Relevance
“…Across the conditions, youth in higher grades outperformed youth in the lower grades on both the amount of correct details recalled and the multiple-choice questions answered correctly. These findings match our predictions, and are consistent with past research demonstrating that age is a strong predictor of ability to comprehend interrogation rights (e.g., Freedman et al, 2014;Goldstein et al, 2003;McLachlan, Roesch, & Douglas, 2011). Although cognitive abilities were not directly assessed in the current study, we suspect that the observed difference between grade levels is due to developmental differences (e.g., working memory, reading skill) between younger and older students (Luna et al, 2004;O'Reilly & McNamara, 2007;Yurgelun-Todd, 2007).…”
Section: V Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Across the conditions, youth in higher grades outperformed youth in the lower grades on both the amount of correct details recalled and the multiple-choice questions answered correctly. These findings match our predictions, and are consistent with past research demonstrating that age is a strong predictor of ability to comprehend interrogation rights (e.g., Freedman et al, 2014;Goldstein et al, 2003;McLachlan, Roesch, & Douglas, 2011). Although cognitive abilities were not directly assessed in the current study, we suspect that the observed difference between grade levels is due to developmental differences (e.g., working memory, reading skill) between younger and older students (Luna et al, 2004;O'Reilly & McNamara, 2007;Yurgelun-Todd, 2007).…”
Section: V Discussionsupporting
confidence: 92%
“…In recognition of their increased vulnerability relative to adults, youth in many Western countries have been afforded enhanced legal protections when faced with a police interrogation. Unfortunately, previous research has shown that the documents used to deliver said rights are overly complex (e.g., Rogers et al, 2012), and therefore youth often struggle to comprehend their legal rights (e.g., Freedman et al, 2014;Grisso, 1981). This lack of comprehension suggests that the enhanced legal protections-as they are currently delivered-are ineffectual in actually protecting youth.…”
Section: V Discussionmentioning
confidence: 99%
See 3 more Smart Citations